Comparing the effect of individual counseling with counseling on social application on self-care and quality of life of women with gestational diabetes. Issue 5 (October 2021) - Ghasemi, Fatemeh; Vakilian, Katayon; Khalajinia, Zohre
Highlights: This interventional study was done on women with gestational diabetes. Face-to-face consoling and on social application were done to improved self-care and quality of life. Counseling was performed in four 45-min sessions in the pregnancy weeks of 27, 28, 29, and 30. Self-care behaviors was higher in face-to-face counseling group than social application. Abstract: Introduction: The present study aimed to compare the effect of two different forms of face-to-face and counseling on a social application, i.e., WhatsApp, on self-care and quality of life of women with gestational diabetes. Methods: The present research was an educational trial with control group, which was conducted on diabetic women between 24 and 26 weeks of pregnancy. A total of 126 subjects were included in the study using the convenient sampling method. They were assigned into three groups. All of the participants answered the questionnaires gestational diabetes self-care, and quality of life at the beginning and end of the study. The GATHER approach to counseling (G = Greeting, A = Ask, T = Tell, H = Help, R = Return) was performed in four 45-min sessions for face-to-face and WhatsApp groups in the pregnancy weeks of 27, 28, 29, and 30. The subjects in the control group received only the routine cares for gestational diabetes. T test, Chi squared test, and ANOVA repeated measurement test were used to analyze the data. Results: Findings showed a significant difference among the three groups in self-care and quality of life (p = 0.001). There was also a significant difference among the three groups in fasting blood sugar after the intervention (p = 0.005). Conclusion: Self-care counseling, both in the form of face-to-face and on social networks, improved the score of self-care and quality of life as well as glucose tolerance test (GTT) in women with gestational diabetes.